Combined treatment with CDK4/6, CDK2, and CXCR1/2 inhibitors effectively halts the growth of BRAF wild-type melanoma tumors - Yang, Jinming; Luo, Weifeng; Ward, Patricia; Chen, Sheau-Chiann; Zebala, John; Maeda, Dean; Yan, Chi; Richmond, Ann (Frontiers in Oncology, 2025)
IntroductionInhibitors of cyclin-dependent kinase 4 and 6 (CDK4/6) are approved for the treatment of locally advanced or metastatic breast cancer, but not for melanoma.MethodsIn this study, we evaluated the effectiveness of the CDK4/6 inhibitor, palbociclib, the CDK2 inhibitor, PF-07104091, the dual CXCR1 and CXCR2 (CXCR1/2) antagonist, SX-682, and the combination of these inhibitors for effective treatment of melanoma in preclinical models.ResultsBoth palbociclib and SX-682 inhibited the growth of BRAFWT/NRASWT B16-F10 and NRASmut 1014 melanoma tumors and in both models, SX-682 created a more anti-tumor immune microenvironment. The combination effect was additive in the B16F10 model, but not in the 1014 model. In the B16F10 model, the addition of the CDK2 inhibitor, PF-07104091, overcame B16F10 acquired resistance to CDK4/6 inhibitors by suppressing the induction of cyclin D1 and E1 expression by palbociclib. In the less responsive 1014 cells, cyclin D1 was reduced, but cyclin E1 was induced in response to PF-07104091. However, in both models, combined treatment with palbociclib and PF-07104091 markedly suppressed cyclin A2, cyclin D1, cyclin E1 and pRB-S807/S811. Combining CDK4/6 and CDK2 inhibitors with the CXCR1/2 antagonist, SX-682, halted B16F10 tumor growth by blocking tumor cell proliferation and increasing the anti-tumor immune response in the tumor microenvironment.ConclusionsThe combination of all three inhibitors resulted in a tumor microenvironment characterized by increased IFNγ-producing CD4+ T cells, decreased CD4+FOXP3+ T regulatory cells (Tregs), and decreased IL-10-producing CD4+ T cells. This combination also decreased the percentage of CD8+ T cells that expressed PD-1 or TIM-3 and increased the ratio of MHCII+F4/80+ M1-like macrophages to CD206+F4/80+ M2-like macrophages. These data suggest that inhibiting CDK4/6 and CDK2, combined with antagonism of CXCR1/2, may be an effective treatment for BRAF wild-type melanoma tumors and NRAS mutant melanoma tumors that express Rb and are resistant to immune checkpoint inhibitors.